Tinjauan fikih dan astronomis penyatuan matla’: menelusuri pemikiran M.S. Odeh tentang ragam penyatuan matla’ - Muh Nashiruddin (State Institute of Islamic Studies (IAIN) Salatiga, 2012)
The basis of calendar unification or matla constitutes one of the most significant issues relating to the unification effort of Hijra calendar. The popular basis of unification, so far, is based on the union of regional and global matla‘. The division of matla‘ to regional and global matla‘ is now no longer accurate because it can not accommodate the Hijra calendar pooling ideas in the Islamic world. This paper discusses one of the leading International astronomy thought, Mohammad Shawkat Odeh on varieties of matla‘ unification. He divided the principle of matla unification in to five forms: unification of global matla‘ (one matla’ for the whole world); the unity of matla‘ in the regions corresponding visibility of hilal; the unity of matla‘ in a similar area of visibility of hilal; the unity of zonal/partial matla‘; and the unity of local matla‘. Odeh’s thought on the various divisions of matla constitutes new thinking on the concept matla‘ astronomical calculations. He also has presented more detailed thoughts on the division of matla‘ rather than the others.